How Large are Search Frictions? - Pieter A. Gautier; Coen N. Teulings (Tinbergen Institute, 2003)
This paper shows that we can normalize job and worker characteristics so that, without frictions,there exists a linear relationship between wages on the one hand and worker and job type indiceson the other. However, for five European countries and the United States we find strong evidencefor a systematic concave relationship. An assignment model with search frictions provides aparsimonious explanation for our findings. This model yields two restrictions on the coefficientsthat fit the data well. Allowing for unobserved heterogeneity and measurement error, we findthat reservation wages are 25% lower than they would be in a frictionless world. Our resultsrelate to the literature on industry wage differentials and on structural identification in hedonicmodels.
Keywords: J21; J30; J60; J23; 330; wages; search; assignment.; Suchtheorie; Lohntheorie; Suchtheorie; Theorie